2018
DOI: 10.17159/1727-3781/2018/v21i0a1368
|View full text |Cite
|
Sign up to set email alerts
|

Facing the Challenge of Improving the Legal Writing Skills of Educationally Disadvantaged Law Students in a South African Law School

Abstract: Many first-year students in the School of Law at the University of KwaZulu-Natal, Howard College, who have been disadvantaged by a poor primary and secondary education, exhibit poor legal writing skills. Over a period of four years, in order to address this urgent need for legal writing instruction, the School of Law introduced two successive legal writing interventions. The first intervention was the Concise Writing Programme, followed by the Integrated Skills in Context Programme. The Concise Writing Program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Although both types of approaches have certain advantages and disadvantages (Flowerdew, 2016), it seems that there is an increasing tendency to situate literacy interventions, especially at South African tertiary institutions, within the context of the discourses of specific academic disciplines (Boughey, 2002;Butler, 2013: 71;Clarence, 2012;Goodier and Parkinson, 2005;Parkinson, 2000;Van Schalkwyk et al, 2009). Regarding law student training in particular, Crocker (2018) confirms the potential inadequacy of generic writing instruction and interventions. In a study where firstyear law students at the University of Kwazulu-Natal were initially only exposed to a generic writing intervention, it was indeed found that they "not only lacked the motivation to learn generic English writing skills, but that they also did not find it is easy to transfer these skills to the more specific legal writing environment" (Crocker, 2018: 1).…”
Section: Discipline-specific Literacy Interventionsmentioning
confidence: 95%
See 2 more Smart Citations
“…Although both types of approaches have certain advantages and disadvantages (Flowerdew, 2016), it seems that there is an increasing tendency to situate literacy interventions, especially at South African tertiary institutions, within the context of the discourses of specific academic disciplines (Boughey, 2002;Butler, 2013: 71;Clarence, 2012;Goodier and Parkinson, 2005;Parkinson, 2000;Van Schalkwyk et al, 2009). Regarding law student training in particular, Crocker (2018) confirms the potential inadequacy of generic writing instruction and interventions. In a study where firstyear law students at the University of Kwazulu-Natal were initially only exposed to a generic writing intervention, it was indeed found that they "not only lacked the motivation to learn generic English writing skills, but that they also did not find it is easy to transfer these skills to the more specific legal writing environment" (Crocker, 2018: 1).…”
Section: Discipline-specific Literacy Interventionsmentioning
confidence: 95%
“…Despite its importance, the general feeling among academics is that the writing skills of law students and practitioners leave much to be desired (Campbell, 2014;Crocker 2018;Kosse & ButleRitchie, 2003;Louw & Broodryk, 2016;Snyman-Van Deventer & Swanepoel, 2013). This state of affairs is worrying, given the fact that effective writing in law involves the ability to communicate clearly, precisely and fully (Broodryk, 2014: 454).…”
Section: Developing Graduate Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, "lawyers make their living through the effective use of words" (Vinson, 2005, p. 507-508). Nevertheless, in one study, first-year law students at the University of Kwazulu-Natal exemplified the lack of the motivation to learn general English writing skills (Crocker, 2018). A study by Campbell (2014) indicated that many matriculants in South Africa lacked language and literacy skills to embark on legal study, and the incompetency in these basic skills resulted in the low completion rate of Bachelor of Laws.…”
Section: Writing and Law Studentsmentioning
confidence: 99%
“…are attempting to develop student writing (for example,Swanepoel and Snyman-van Deventer 2012; Clarence, Albertus and Mwabene: 2013;Broodryk 2014 Broodryk , 2015Crocker 2018;Gottlieb and Greenbaum 2018;Snyman-van Deventer and van Niekerk 2018;Bangeni and Greenbaum 2019; and Crocker 2020, 2021).…”
mentioning
confidence: 99%